A Simple and Efficient Synthesis of Dibenzothiophene via BF3·OEt2-Promoted Intramolecular Annulation - Shang, Xiaobo; Chen, Wanzhi; Yao, Yingming (Synlett, 2013)
A simple and efficient protocol promoted by BF3·OEt2 for synthesizing functionalized dibenzothiophenes (DBTs) has been demonstrated. The annulation condition can tolerate a variety of functional groups.
Keywords: dibenzothiophenes; cyclization; Lewis acid; triazene